“An Analysis of Politeness Maxim Based on Leech’s Principles In the Movie Fawlty Towers: The Hotel Inspectors” - Muzaqi, Ahmad Imam (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study analyzes the politeness of maxim reflected in a comedy movie. This study investigated whether the maxim principles conceptualized by Leech (1983) are reflected in the Movie “Fawlty Towers”. The movie is a stream of comedy story series and provides the impression of daily conversation, with interesting speech acts to learn. The data of this study were the dialogues spoken by characters obtained from the script of the movie. The results yielded the most relevant to the polite maxim. Its maxim included all principles such as tact, generosity, approbation, modesty, and agreement, while the sympathy maxim was not shown in this movie. The study found that maximum levels in this movie could be alternated or changed under the conditions of polite speakers in communicating with the interlocutors.